Involuntary Absence from an Organizational Point of View - Jan M.P. de Kok (Tinbergen Institute, 1997)
Involuntary absence is often seen as an exogenous factor, but firms can take actions to reduceit. In this paper the notion that firms, especially SMEs, are faced with a single decisionwhether or not to undertake these actions is questioned. A firm model on involuntary absencemeasures is constructed and estimated in which four successive steps are distinguished. Itturns out that this model is supported by the data. Furthermore a clear firm-size effect exists.Larger firms tend to take more precautionary actions than small firms because they havemore attention for work- and health-related topics in general and more easily recognise theinfluence they can exert on the level of involuntary absence.
Keywords: J28; 330; involuntary absenteeism; precautionary measures; SME; Fehlzeit; KMU; Niederlande